Characterization of a midgut mucin-like glycoconjugate of Lutzomyia longipalpis with a potential role in Leishmania attachment. Issue 1 (December 2016) - Myšková, Jitka; Dostálová, Anna; Pěničková, Lucie; Halada, Petr; Bates, Paul; Volf, Petr
Abstract Background Leishmania parasites are transmitted by phlebotomine sand flies and a crucial step in their life-cycle is the binding to the sand fly midgut. Laboratory studies on sand fly competence toLeishmania parasites suggest that the sand flies fall into two groups: several species are termed "specific/restricted" vectors that support the development of oneLeishmania species only, while the others belong to so-called "permissive" vectors susceptible to a wide range ofLeishmania species. In a previous study we revealed a correlation between specificityvs permissivity of the vector and glycosylation of its midgut proteins.Lutzomyia longipalpis and other four permissive species tested possessed O-linked glycoproteins whereas none were detected in three specific vectors examined. Results We used a combination of biochemical, molecular and parasitological approaches to characterize biochemical and biological properties of O-linked glycoprotein ofLu. longipalpis . Lectin blotting and mass spectrometry revealed that this molecule with an apparent molecular weight about 45–50 kDa corresponds to a putative 19 kDa protein with unknown function detected in a midgut cDNA library ofLu. longipalpis. We produced a recombinant glycoprotein rLuloG with molecular weight around 45 kDa. Anti-rLuloG antibodies localize the native glycoprotein on epithelial midgut surface ofLu. longipalpis . Although we could not prove involvement of LuloG inLeishmania attachment by blocking the native protein with anti-rLuloG during sand fly infections, we demonstrated strong binding of rLuloG to whole surface ofLeishmania promastigotes. Conclusions We characterized a novel O-glycoprotein from sand flyLutzomyia longipalpis . It has mucin-like properties and is localized on the luminal side of the midgut epithelium. Recombinant form of the protein binds toLeishmania parasites in vitro. We propose a role of this molecule inLeishmania attachment to sand fly midgut.